Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The functions of repressor element 1-silencing transcription factor in models of epileptogenesis and post-ischemia - Ruth Butler-Ryan; Ian C. Wood (Metabolic Brain Disease, 2021)
Epilepsy is a debilitating neurological disorder characterised by recurrent seizures for which 30% of patients are refractory to current treatments. The genetic and molecular aetiologies behind epilepsy are under investigation with the goal of developing new epilepsy medications. The transcriptional repressor REST (Repressor Element 1-Silencing Transcription factor) is a focus of interest as it is consistently upregulated in epilepsy patients and following brain insult in animal models of epilepsy and ischemia. This review analyses data from different epilepsy models and discusses the contribution of REST to epileptogenesis. We propose that in healthy brains REST acts in a protective manner to homeostatically downregulate increases in excitability, to protect against seizure through downregulation of BDNF (Brain-Derived Neurotrophic Factor) and its receptor, TrkB (Tropomyosin receptor kinase B). However, in epilepsy patients and post-seizure, REST may increase to a larger degree, which allows downregulation of the glutamate receptor subunit GluR2. This leads to AMPA glutamate receptors lacking GluR2 subunits, which have increased permeability to Ca 2+ , causing excitotoxicity, cell death and seizure. This concept highlights therapeutic potential of REST modulation through gene therapy in epilepsy patients.